A new hybrid mathematical model for interference management by combining of fractional frequency reuse and dynamic power control methods in femtocell networks / Mastura Rosdi - Rosdi, Mastura (Institute of Graduate Studies, UiTM, 2017)
The increase in capacity and system data rate may lead to capacity problems and hence become one of the crucial issues in any Mobile Communication Networks. Although the Long Term Evolution (LTE) is called the 4th Generation of the Mobile Cellular Communication Network, it can no longer solve the problem regarding the capacity of the cell. In order to cope with the increase in demand for stable and high data rates among mobile users, femtocell or Home Evolve Node B (HeNB) has been developed to improve indoor capacity and coverage. Deploying femtocells in macrocell are one of the efficient ways to improve the performance of mobile services in high traffic congested areas. Femtocell is a small and lightweight base station that aims for indoor usage such as at home or in an enterprise and provide better user experiences to users. However, femtocell deployments caused interference between femtocells itself and also to the existing macrocells. This thesis studied the two combining interference methods in LTE Heterogeneous Networks (HetNets) in order to reduce interference in HetNets which are the Fractional Frequency Reuse (FFR) and Dynamic Power Control (DPC) methods.